The Impact of the EU General Data Protection Regulation on the Admissibility of Evidence in Lithuanian Civil Procedure - Bartkus, Jurgis (Teisė, 2024)
The article analyses the impact of the EU General Data Protection Regulation on the admissibility of evidence in Lithuanian civil procedure after the judgment of the Court of Justice of the European Union in case C-268/21. The article provides an overview of the requirements of the General Data Protection Regulation for civil proceedings and identifies specific problematic aspects that could unbalance the evidentiary system in Lithuanian civil proceedings.